Effects of turbulence models and grid densities on computational accuracy of flows over a vertical axis wind turbine - Chaiyanupong, Jaruwan; Chitsomboon, Tawit (International Journal of Renewable Energy Development, 2018)
Flows through a vertical axis wind turbine (VAWT) are very complex due to their inherent unsteadiness caused by large variations of the angle of attacks as the turbine is rotating and changing its azimuth angles simultaneously. In addition, a turbine must go through a wide range of operating conditions especially the change in blade speed ratio (BSR). Accurate prediction of flows over VAWT using Reynolds-Averaged Navier-Stokes (RANS) model needs a well-tested turbulence model as well as a careful grid control around the airfoil. This paper aimed to compare various turbulence models and seek the most accurate one. Furthermore, grid convergence was studied using the Roache method to determine the sufficient number of grid elements around the blade section. The three-dimensional grid was generated by extrution from the two-dimensional grid along with the appropriate y+ controlling. Comparisons were made among the three turbulence models that are widely used namely: the RNG model, the shear stress transport k-Ï‰ model (SST) and the Menterâ€™s shear stress transport k-Ï‰ model (transition SST). Results obtained clearly showed that turbulence models significantly affected computational accuracy. The SST turbulence model showed best agreement with reported experimental data at BSR lower than 2.35, while the transition SST model showed better results when BSR is higher than 2.35. In addition, grid extruding technique with y+ control could reduce total grid requirement while maintaining acceptable prediction accuracy.Article History: Received April 15th 2018; Received in revised form June 16th 2018; Accepted September 17th 2018; Available onlineHow to Cite This Article: Chaiyanupong,J and Chitsomboon, T. (2018) Effects of Turbulence Models and Grid Densities on Computational Accuracy of Flows Over a Vertical Axis Wind Turbine. Int. Journal of Renewable Energy Development, 7(3), 213-222.http://dx.doi.org/10.14710/ijred.7.3.213-222Â